1994
DOI: 10.1042/cs0870587
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Bone Mineral Density between Caucasian, Asian and Afro-Caribbean Women

Abstract: 1. We analysed the lumbar spine (L2-L4) and femoral neck bone mineral density results of Caucasian (n = 2232), Asian (Indian sub-continent) (n = 153) and Afro-Caribbean (n = 102) women referred for bone densitometry over a 30 month period. To assess the risk of osteoporosis, the results of Caucasian and Asian women were compared with those of a reference Caucasian population supplied by Lunar. 2. Subject characteristics were similar in all three groups, other than expected ethnic differences in stature and wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
43
0
2

Year Published

1997
1997
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(45 citation statements)
references
References 0 publications
0
43
0
2
Order By: Relevance
“…When bone size was adjusted for, BMAD values at the lumbar spine and femoral neck were actually somewhat greater for Somali than for white women. Likewise, recent studies have shown that adjustment for bone or body size reduces apparent differences in bone density between white and Asian women [31,44,[51][52][53][54][55]. However, this correction did not equilibrate bone density values among those of African heritage, as BMAD values were still significantly greater among AA than Somali women.…”
Section: Discussionmentioning
confidence: 81%
“…When bone size was adjusted for, BMAD values at the lumbar spine and femoral neck were actually somewhat greater for Somali than for white women. Likewise, recent studies have shown that adjustment for bone or body size reduces apparent differences in bone density between white and Asian women [31,44,[51][52][53][54][55]. However, this correction did not equilibrate bone density values among those of African heritage, as BMAD values were still significantly greater among AA than Somali women.…”
Section: Discussionmentioning
confidence: 81%
“…Nevertheless, the large differences in mean UCa between the three ethnic groups (with whites excreting approximately 1.0 mmol per day more calcium in their urine than blacks or S Asians) might help explain the higher bone density of blacks 36 and why osteoporosis 37,38 and bone fractures 39,40 are more common in whites than in blacks or S Asians. Despite these differences the association of UCa with both BP and UNa was independent of ethnic origin.…”
Section: Discussionmentioning
confidence: 99%
“…From an endocrine kinetic standpoint, while menarche or pregnancy may also affects on the BMD (Ozdemir et al 2005), we focused on the time of the menopause and climacteric in the present study. BMC and BMD have been reported to be lower in Asian than Caucasian adults (Tobias et al 1979;Walker et al 2006). These racial differences may be the result of differences in life style, such as food intake and physical exercise.…”
Section: Discussionmentioning
confidence: 99%